Transport properties and enhanced thermoelectric performance of aluminum doped Cu3SbSe4. Issue 40 (2nd April 2015) - Li, Yuanyue; Qin, Xiaoying; Li, Di; Li, Xiyu; Liu, Yongfei; Zhang, Jian; Song, Chunjun; Xin, Hongxing
Abstract : The electrical transport and thermoelectric properties of Cu3 Sb1− x Al x Se4 ( x = 0, 0.01, 0.02 and 0.03) compounds are investigated in the temperature range of 300–600 K. Abstract : The electrical transport and thermoelectric properties of Cu3 Sb1− x Al x Se4 ( x = 0, 0.01, 0.02 and 0.03) compounds are investigated in the temperature range of 300–600 K. The results indicate that with increasing Al content from x = 0 to x = 0.03, hole concentration increases monotonically from 8.04 × 10 17 to 1.19 × 10 19 cm −3 due to the substitution of Al 3+ for Sb 5+, thus leading to a large decrease in the electrical resistivity of Cu3 Sb1− x Al x Se4 . Meanwhile, the increase in hole concentration leads to a transition from a non-degenerate ( x = 0) to a partial degenerate ( x = 0.01, 0.02) and then to a degenerate state ( x = 0.03). The power factor (PF) of all the Al-doped Cu3 Sb1− x Al x Se4 samples is remarkably improved due to the optimization of hole concentration. Lattice thermal conductivity κ L of the heavily doped sample ( x = 0.03) is reduced. As a result, a large thermoelectric figure of merit ZT = 0.58 is obtained for Cu3 Sb0.97 Al0.03 Se4 at 600 K, which is around 1.9 times as large as that of the un-doped Cu3 SbSe4 .